Factors Causing Landslides on Highways in Ogan Komering Ulu Regency, South Sumatra Province - Dewi, Anggi Purnama Sari; Iqbal, Maulid M; Sutejo, Yulindasari; Dewi, Ratna; Adhityia, Bimo (International Journal of Innovative Research and Scientific Studies, 2022)
This research focuses on the study of a slope’s Factor of Safety (FOS) in the context of landslides. The slopes under study are located on the outer bend of a river and feature differences in groundwater levels on the slope and outside the slope. This research was conducted on Jalan Kol. Burlian STA 429+312 (case 1) and connecting road IV STA 194+420 (case 2) in OKU Regency, South Sumatra Province, Indonesia. The analysis was carried out using the Slope/W program to obtain the FOS to discover the cause of the landslide. The results of the Slope/W program (Fellenius method) provided an initial condition FOS value for case study 1 of 1.70, and a FOS value after scouring of 1.12. For case study 2 the initial condition FOS value was 1.68, and after scouring 1.05. Based on the results of the analysis, it can be concluded that the cause of the landslide is the occurrence of scouring and the presence of GWT.